2022
DOI: 10.1177/09721509221116692
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Enterprise Resource Planning System Implementation on Accrual-Based Earnings Management: Empirical Evidence from Jordan

Abstract: This research provides evidence on whether enterprise resource planning (ERP) implementation affects accrual-based earnings management (AEM) in the service and manufacturing firms listed on the Amman Stock Exchange (ASE). The Huber–White’s sandwich estimator for pooled ordinary least squares (OLS) regression was utilized for this investigation as the primary statistical technique. Using three different AEM models and a sample of 390 firm-year observations for the period spanning from 2015 to 2019, this study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The present research includes service and manufacturing companies listed on Amman Stock Exchange (ASE) during the period 2019 to 2022. Financial firms were eliminated from the analysis since they are subject to distinct rules and regulations than non-financial companies (Abu Afifa et al, 2022; Mansour et al, 2022; Toumeh, 2022). Nevertheless, incorporating the service sector alongside manufacturing in the sample is essential for a comprehensive analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The present research includes service and manufacturing companies listed on Amman Stock Exchange (ASE) during the period 2019 to 2022. Financial firms were eliminated from the analysis since they are subject to distinct rules and regulations than non-financial companies (Abu Afifa et al, 2022; Mansour et al, 2022; Toumeh, 2022). Nevertheless, incorporating the service sector alongside manufacturing in the sample is essential for a comprehensive analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Research done by Dehning et al (2017); Morris & Laksmana (2010); Patnaik et al (2019); Tsai et al (2012) revealed that after the implementation of ERP, there was an improvement in information quality due to declining earnings management. A more recent study regarding the effect of implementing ERP systems and earnings management was conducted by Toumeh (2022). The study suggests that ERP implementation is associated with decreased accrual-based earnings management in Jordanian firms.…”
Section: Literature Review and Hypothesis Development Agency Theorymentioning
confidence: 99%
“…The study suggests that ERP implementation is associated with decreased accrual-based earnings management in Jordanian firms. This implies that companies using ERPs tend to manipulate financial statements less through accounting choices (Toumeh, 2022). However, implementing ERP systems is not without any risk.…”
Section: Literature Review and Hypothesis Development Agency Theorymentioning
confidence: 99%
“…In pursuit of understanding the impact of ERP implementation on the quality of corporate financial reporting, the majority of studies have adopted accrual earnings management as a proxy variable for earnings quality. (Morris and Laksmana, 2010;Toumeh, 2022;Tsai et al, 2012;Chen, 2012). Morris and Laksmana (2010) examined the impact of ERP systems on earnings management, comparing levels for 143 firms in 32 industry groups that implemented ERP systems between 1994 and 2003 to levels for a control group.…”
Section: Erp Utilization and Earnings Management Hypothesis Developmentmentioning
confidence: 99%